Assessing STEM Career Interest among Senior High School Students: Implementation of the STEM-CIS in the Pilot of the Strengthened SHS Curriculum - Karl Evan Pama (Future Science / FSH-PH Publications, 2026)
This study determined how much Grade 11 students are interested in Science, Technology, Engineering, and Mathematics (STEM) careers. The students were part of the new Strengthened Senior High School Curriculum in the Philippines for School Year 2025–2026. A total of 455 students answered a survey about how they feel relative to STEM careers. The results showed respondents’ high interest in science, technology, and math careers, but their interest in engineering jobs was not as high. In terms of career pathways, students who chose Health and Wellness Sciences liked science the most, and students in Engineering and Natural Sciences liked technology and engineering more. Students in Business and Accounting were the most interested in math. As to sex assigned at birth (i.e., male and female), it was found that both were almost the same in liking science and math, but males were more interested in technology and engineering than females. It can be summarized that students were already interested in STEM, especially when their studies match the career they want in the future. Because of this, even though strands are no longer part of the Strengthened SHS Curriculum, schools are encouraged to provide more hands-on STEM opportunities and experiences to all students so everyone can uncover their talents and gain higher confidence in STEM activities. More students can grow up to become future scientists, engineers, doctors, and innovators who will help improve the country.